Analysis of The Implementation of The Education Council Program in Advancing Education in Kendari City - anidi saidi (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2021)
This study aims to describe the implementation of the program implemented by the Education Council in advancing education in Kendari City in January - June 2020. This research is a qualitative descriptive study, with data collection techniques used, namely observation, interviews, and documentation. The data analysis technique this study uses is the Miles & Huberman analysis technique; namely, the analysis consists of three streams of activities that co-occur: data reduction, data presentation, and conclusion drawing/verification. The study results show that the Education Council's January-June 2020 program to advance education includes: (a) assistance in the implementation of education; and (b) strengthening the institutional relationship of the education board with interested parties.